Penerapan Metode VIKOR Dalam Penentuan Penerimaan Dana Bantuan Rumah Tidak Layak Huni - Manurung, Hotben; Damanik, Irfan Sudahri; Saragih, Ilham Syahputra (TIN: Terapan Informatika Nusantara, 2021)
The provision of grants is a program given by the government to the less fortunate. A grant program is held to assist the community in the survival of the community, especially in housing issues. The provision of home assistance is done selectively in accordance with the assistance provided. One of the help offered is uninhabitable Home Assistance (RUTILAHU). In this study used the VIKOR method so that the results obtained are expected to assist the government in managing the RUTILAHU Relief Fund to decide the eligible beneficiar To help and improve community welfare, the government created a RUTILAHU assistance program through the Simalungun District Social Service. The RUTILAHU program is carried out to assist the poor in repairing their homes, which are in dire condition. Mistakes have been a subjective cost. It is feared that this will lead to inaccuracy in selecting potential recipients of RUTILAHU assistance. Therefore, researchers built a decision support system to determine recipients of RUTILAHU assistance using the vicar method. The criteria used are stage, wall condition, roof condition, floor condition, medical ability, ability to buy clothes, ownership of toilets, floor area, water source, land ownership, source of lighting, occupation, number of family members, and number of members. Based on the test results, the system built can help the Simalungun District Social Service in determining potential recipients of RUTILAHU assistance quickly and easily with objective results